A Review: Nanoparticles NiFe2O4 Synthesis and Its Application as Hyperthermia Agents in Biomedicine (Indonesian Journal of Chemical Science, 2022)
Nickel ferrite (NiFe2O4) is one of the spinel ferrite nanoparticles that is useful for scientific and technological, like biomedicine. This paper discusses the synthesis of NiFe2O4 nanoparticles by various methods. This paper aims to find out the most efficient method for the synthesis of NiFe2O4 nanoparticles which are used as hyperthermia agents in biomedicine. The method used is a literature study of an article with publications from 1956-2018 by discussing several methods of NiFe2O4 syntheses, such as sol-gel, hydrothermal, co-precipitation, and combustion. From these methods, it was found that co-precipitation is the most efficient method among the other methods because it produces a relatively small NiFe2O4 nanoparticle size, which is 28 nm, causing these small particles to tend to be superparamagnetic and is good to be used as hyperthermia agent in biomedicine. This study is expected to be used as a reference to determine the method for synthesizing NiFe2O4 nanoparticles.